Pengembangan Kemampuan Motorik Kasar Berbasis Permainan Tradisional Lompat Tali pada Usia 4-5 tahun - Fadilatul Fitria; Amidanal Chikmah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Gross motor refers to the ability of large movements or motor skills that involve the use of large muscles in the body to perform physical activities. One way to develop gross motor skills is through traditional games. Traditional games refer to games that have existed and are played by the community from generation to generation. These games reflect the cultural heritage of each region. One of the heritage games in Java is Jump rope. This research aims to help children's gross motor development based on traditional jump rope games. At the age of 4-5 years, children make significant progress in their gross motor development. It is important to note that each child has a unique development and is different from one another, hence the need for a response from the environment to help optimize children's growth and development. The research method used in this study is classroom action research with 20 children. From the results of the research that has been carried out, gross motor development based on traditional jump rope games is proven to optimize the motor development of children aged 4-5 years, it can be seen by an increase in the percentage which initially only 7% increased to 25% in cycle 1, and 80% in cycle 2.